In our time: Memoir of a revolution - Brownmiller, Susan (Dial Press, 1999)
There once was a time when the concept of equal pay for equal work did not exist, when women of all ages were "girls," when abortion was a back-alley procedure, when there was no such thing as a rape crisis center or a shelter for battered women, when "sexual harassment" had not yet been named and defined. "If conditions are right," Susan Brownmiller says in this stunning memoir, "if the anger of enough people has reached the boiling point, the exploding passion can ignite a societal transformation." In Our Time tells the story of that transformation, as only Brownmiller can. A leading feminist activist and the author of Against Our Will, the book that changed the nation's perception of rape, she now brings the Women's Liberation movement and its passionate history vividly to life. Here is the colorful cast of characters on whose shoulders we stand–the feminist icons Betty Friedan, Kate Millett, Germaine Greer, and Gloria Steinem, and the lesser known women whose contributions to change were equally profound. And here are the landmark events of the era: the consciousness-raising groups that sprung up in people's living rooms, the mimeographed position papers that first articulated the new thinking, the abortion and rape speak-outs, the daring sit-ins, the underground newspaper collectives, and the inventive lawsuits that all played a role in the most wide-reaching revolution of the twentieth century. Here as well are Brownmiller's reflections on the feminist utopian vision, and her dramatic accounts, rendered with honesty and humor, of the movement's painful internal schisms as it struggled to give voice to the aspirarations of all women. Finally, Brownmiller addresses that most relevant question: What is the legacy of feminism today?
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; droits des femmes*; fem1000; féminisme matérialiste; féminisme radical; histoire; mouvements féministes; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; témoignage; états-unis

Théoriser le genre : l'héritage de Beauvoir - Jackson, Stevi (Nouvelles Questions Féministes, 1999)
En déclarant qu' "on ne naît pas femme, on le devient", Simone de Beauvoir a posé les fondements d'une conception féministe du genre. L'analyse développée dans Le Deuxième sexe a anticipé la distinction ultérieure entre sexe et genre, et a également soulevé certains problèmes liés à cette distinction. Plutôt que l'oeuvre même de Beauvoir, ce sont les discussions récentes autour de la distinction sexe/genre qui font l'objet de cet article. Plus particulièrement, j'examine la manière dont les féministes matérialistes françaises, avec qui Beauvoir elle-même a travaillé, ont fait fructifier son héritage. En affirmant que le "sexe" est un phénomène tout aussi social que le "genre", ces féministes ont maintenu une tradition anti-essentialiste fondamentalement opposée aux perspectives "différentialistes" si souvent associées à la construction anglophone du "French feminism". Je confronte la contribution de ces féministes, notamment Christine Delphy et Monique Wittig, aux conceptions féministes du genre, avec l'approche plus déconstructive associée à des théoriciennes comme Judith Butler. Ce faisant, je plaide pour une analyse matérialiste du genre et pour une vision d'un monde sans genre plutôt que d'un monde avec de multiples genres. In claiming that 'one is not born, but rather becomes, a woman', Simone de Beauvoir laid the foundations for a feminist understanding of gender. The analysis developed in The Second Sex anticipated the later distinction between sex and gender, and also evinced some of the problems associated with that distinction. It is these more recent discussions of the sex/gender distinction which are the focus of this paper, rather than Beauvoir's work itself. More specifically, I consider the ways in which French materialist feminists, with whom Beauvoir herself worked, carry forward her legacy. In arguing that ' sex' is as much a social phenomenon as 'gender', these feminists have kept alive an anti-essentialist tradition which is fundamentally opposed to the 'difference' perspectives so often associated with the anglophone construction of ' French Feminism'. I compare the contribution that these feminists, especially Christine Delphy and Monique Wittig, have made to feminist understandings of gender with the more deconstructive approach associated with thinkers such as Judith Butler. In so doing I argue the case for a materialist analysis of gender and for a vision of a world without gender rather than a world with many genders.
https://www.jstor.org/stable/40619720
Keywords: 1900-1999; approches et analyses; cours; discipline; fem1000; france; féminisme matérialiste; genre; histoire; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes